2017
DOI: 10.1111/vec.12583
|View full text |Cite
|
Sign up to set email alerts
|

Use of cryopoor plasma for albumin replacement and continuous antimicrobial infusion for treatment of septic peritonitis in a dog

Abstract: This case includes novel techniques such food dye via nasogastric tube to identify anastomosis dehiscence, use of CPP as a source of canine albumin, and antimicrobial CRI in a dog with septic peritonitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…We showed that survivors received approximately 4 interventions out of 7 possible, whereas nonsurvivors received approximately 2 of those interventions, although there were not enough data to decipher a further breakdown of the bundle. 9 Our data support, specifically, that early antimicrobial administration is beneficial in septic shock patients, with patient whom received antimicrobials within 3 hours having a 35% survival rate, which is close to the current survival rate in people. 12 There is a significant amount of data in both the human and veterinary literature suggesting that early and appropriate antimicrobial therapy is an important determinant of outcome in septic patients.…”
Section: F I G U R Esupporting
confidence: 77%
See 4 more Smart Citations
“…We showed that survivors received approximately 4 interventions out of 7 possible, whereas nonsurvivors received approximately 2 of those interventions, although there were not enough data to decipher a further breakdown of the bundle. 9 Our data support, specifically, that early antimicrobial administration is beneficial in septic shock patients, with patient whom received antimicrobials within 3 hours having a 35% survival rate, which is close to the current survival rate in people. 12 There is a significant amount of data in both the human and veterinary literature suggesting that early and appropriate antimicrobial therapy is an important determinant of outcome in septic patients.…”
Section: F I G U R Esupporting
confidence: 77%
“…Our current study investigated the impact of interventions that have been linked to an improved outcome in humans suffering from septic shock or may be beneficial for those patients in a bundle approach. We showed that survivors received approximately 4 interventions out of 7 possible, whereas nonsurvivors received approximately 2 of those interventions, although there were not enough data to decipher a further breakdown of the bundle 9 …”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations